2021
DOI: 10.1097/ogx.0000000000000927
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Cancer Screening in the United States: Challenges and Potential Solutions for Underscreened Groups

Abstract: real-time laparoscopic assessment by the original surgeons and subsequent review of digital images by expert surgeons. The experts were directors of laparoscopic gynecologic training programs in North America with extensive experience in endometriosis diagnosis and management. Other data sources were added sequentially (operative reports, MRI results, and histopathology) to assess their value in obtaining higher interrater agreement. Mean agreement based on digital images alone was acceptable (0.67), increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Future research could seek the views of gender‐diverse Māori, as HPV self‐testing has been found to be acceptable for transmasculine individuals internationally 37 . It has also been suggested that HPV self‐testing may help to address barriers to cervical screening for disabled people and people living with co‐morbid conditions, 38 which could be explored for Māori.…”
Section: Discussionmentioning
confidence: 99%
“…Future research could seek the views of gender‐diverse Māori, as HPV self‐testing has been found to be acceptable for transmasculine individuals internationally 37 . It has also been suggested that HPV self‐testing may help to address barriers to cervical screening for disabled people and people living with co‐morbid conditions, 38 which could be explored for Māori.…”
Section: Discussionmentioning
confidence: 99%
“…They noted that while this barrier seemed a single distinctive factor for women in low socioeconomic status in Latin America, the Hispanic women with low socioeconomic status in Canada do not report this because most of them have a physician whom they consult regularly, and the country has a national public health care system 38 . Worthy of note, while the lack of time due to competing demands, difficulty finding childcare, remembering to make and/or attend an appointment, transportation cost, and language barrier were the confounding factors to screening service accessibility among underserved groups (rural residents, immigrants, racial/ethnic minority groups, unemployed women, those who speak a language other than English) in the United States 44 ; in Nigeria, the non-existence of screening facilities in most regions of the country poses a major challenge to screening accessibility. Financial constraint is another factor that poses a barrier to the uptake of screening, and it was associated with the need for spousal approval in one study 22 .…”
Section: Key Findingsmentioning
confidence: 99%
“…Future research could seek the views of gender-diverse Pasifika, since HPV self-testing has been found to be acceptable for transmasculine individuals internationally. 23 HPV selftesting may also help to address barriers to cervical screening for people with comorbid conditions and disabled people 24 ; these could also be explored among Pasifika.…”
Section: Strengths and Limitationsmentioning
confidence: 99%